Cognitive Factors as a Key to Plain-Sense Biblical Interpretation: Resolving Cruxes in Gen 18:1–15 and 32:23–33 - Stein, David E. S. (Open theology, 2018)
Both the accounts of Abraham’s three visitors (Gen 18:1-15) and of Jacob’s nighttime intruder (32:23- 33) are famous interpretive cruxes. This article shows why the plain sense is that both Abraham and Jacob recognize right away that the newly introduced figures represent their deity. It does this by: (1) accounting for the place of messengers in the mental life of ancient Israel; (2) recovering an under-appreciated yet cognitively based narrative convention regarding messengers; (3) setting the starting point of each narrative with care; (4) attending to the semantics and pragmatics of the main noun in both accounts; and (5) emulating the online processing of language that an audience’s mind automatically employs, which is incremental and prediction-driven. In the emulation exercise, the audience’s mental parser arrives at a "recipient recognition" (RR) construal quickly-already before the end of 18:2, and by the end of 32:25. Furthermore, handling 32:25 in this manner resolves a third crux at the same time (32:2-3). An RR construal is cognitively favored because it yields a coherent and informative text, unlike the "obscured origin" (OO) construal that theologians presently favor. Meanwhile, the emulation validates a previously proposed hypothesis that the noun אִישׁ ’îš functions as the generic label for designating an "agent"-that is, someone who is representing the interests of another party. All told, this article employs a variety of cognitive factors as keys to plain-sense interpretation. Finally, it touches upon the theological implications of the RR construal of the two passages under study.